2006
DOI: 10.1021/la053289c
|View full text |Cite
|
Sign up to set email alerts
|

Stable Modification of PDMS Surface Properties by Plasma Polymerization:  Application to the Formation of Double Emulsions in Microfluidic Systems

Abstract: We describe a method based on plasma polymerization for the modification and control of the surface properties of poly(dimethylsiloxane) (PDMS) surfaces. By depositing plasma polymerized acrylic acid coatings on PDMS, we succeeded to fabricate stable (several days) hydrophilic and patterned hydrophobic/hydrophilic surfaces. We used this approach to generate direct and (for the first time in this material) double emulsions in PDMS microchannels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
131
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(139 citation statements)
references
References 21 publications
3
131
0
1
Order By: Relevance
“…A timing difference can occur when droplet production in coupled droplet generators is not synchronous, as Barbier et al have characterized experimentally for a wide range of conditions. 47 Although we do not take steps to avoid timing differences, such non-synchronous behavior can be a limitation to the practical use of devices such as these.…”
Section: Observations Of Droplet Collisions At T-junctionsmentioning
confidence: 99%
“…A timing difference can occur when droplet production in coupled droplet generators is not synchronous, as Barbier et al have characterized experimentally for a wide range of conditions. 47 Although we do not take steps to avoid timing differences, such non-synchronous behavior can be a limitation to the practical use of devices such as these.…”
Section: Observations Of Droplet Collisions At T-junctionsmentioning
confidence: 99%
“…Barbier et al [92] deposited 200 µm lines of ppPAcAc onto PDMS, using a masking technique similar to what is described in earlier paragraphs. These patterned surfaces were then successfully implemented into a microfluidic device to transport direct and double emulsions, which was first tried for PDMS samples and is shown in Figure 7.…”
Section: Cooh-rich Geometric Domainsmentioning
confidence: 99%
“…Further analysis revealed that the adsorption of Ca 2+ played a critical role in the selection and that only cell-lines, such as the RINm5f tumour cells, which express Ca 2+ dependant membrane proteins are susceptible to the applied pattern. Source: Barbier et al [92] Finally Filova et al [94] did an extensive study on the cell response of four different cell types (rat smooth muscle cells, human and porcine skeletal muscle cells and bovine endothelial cells) to patterns generated via the plasma polymerisation of ppAcAc and 1,7-octadiene. A TEM grid was used to generate tracks of approximately 100 µm.…”
Section: Cooh-rich Geometric Domainsmentioning
confidence: 99%
“…Kovach and his co-workers [29] achieved long term hydrophilicity and hemocompatibility of PDMS microchannels using a plasma-assisted polyethylene glycol (PEG) grafting. Barbier et al [30] deposited plasma polymerized acrylic acid coatings onto unbonded PDMS and implemented for the first time a system to form double emulsions in microchips. This method, though, was performed in vacuum with limitations for implementing on a laboratory scale due its expense.…”
Section: Introductionmentioning
confidence: 99%